1995
DOI: 10.1016/0959-4752(94)00015-h
|View full text |Cite
|
Sign up to set email alerts
|

Learning for later teaching: An exploration of mediational links between teaching expectancy and learning results

Abstract: It was investigated to what extent the expectancy of a teaching demand influences learning results. In addition, possible mediator effects were explored. Thirty-six subjects (students of education) learned from worked-out examples in the domain of probability calculus under two different conditions: The experimental group expected to be required to explain similar worked-out examples to a third person, whereas the control group merely anticipated to be tested on similar problems. The results showed that the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 19 publications
2
50
2
3
Order By: Relevance
“…On the other hand, studying examples with varying surface structures fosters transfer Paas & VanMerrienboer, 1994), and thus a positive relation also seems plausible. Renkl (1995) found a nonsignificant positive association between number of examples and learning gains. In the present study, the extent to which the control variable "number of examples inspected" is related to learning is examined for the case where indicators of the superficiality of processing taken from the verbal protocols are controlled.…”
Section: Worked-out Examplesmentioning
confidence: 87%
“…On the other hand, studying examples with varying surface structures fosters transfer Paas & VanMerrienboer, 1994), and thus a positive relation also seems plausible. Renkl (1995) found a nonsignificant positive association between number of examples and learning gains. In the present study, the extent to which the control variable "number of examples inspected" is related to learning is examined for the case where indicators of the superficiality of processing taken from the verbal protocols are controlled.…”
Section: Worked-out Examplesmentioning
confidence: 87%
“…Several studies have reported empirical evidence of the beneficial effect of explanation expectancy (Annis, 1983;Bargh & Schul, 1980;Benware & Deci, 1984;Fiorella & Mayer, 2013;Sugie & Kajita, 1989). However, this enhancement has not been consistently demonstrated in other studies that have manipulated expectancy (Ehly, Keith, & Bratton, 1987;Fukaya, 2013;Ito & Kakihana, 2009;Renkl, 1995;Schommer, Crouse, & Rhodes, 1992), and the reasons for these inconsistent results are quite unclear (Renkl, 1995).…”
Section: Introductionmentioning
confidence: 67%
“…We must note, however, that in this study, participants were only required to write an explanation. Although Renkl (1995) did not clarify this point, the anxiety effect should be smaller with written explanation compared to oral explanation in the presence of another person. Therefore we did not consider that anxiety effect could fully explain the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in contrast to the cyclical rotation groups, the learners in the expert groups are aware of the demand to teach their peers in the jigsaw group ('teaching expectancy', Renkl, 1995) and they subsequently teach each other. Second, due to the task-specialisation in the jigsaw setting, each group member is accountable for a unique part of the activity and the students in the jigsaw groups are dependent on their experts' knowledge.…”
Section: Introductionmentioning
confidence: 99%